Effect of crystallization method on the formation of carbamazepine-saccharin co-crystal - Syarifah, Abd Rahim; Nur Amanina, Mohamad Adaris (Elsevier Ltd, 2018)
Co-crystallization is a method in formulation of drug products which is believed to improve drugs solubility, stability and dissolution rate while maintaining the biological functions of its chemical properties. In this work, the carbamazepine-saccharin (CBZ-SAC) co-crystal formation using varies mol ratio of SAC to CBZ, ethyl acetate and formic acid as a solvent and two methods was studied. The physical characterization of the co-crystal was characterized using x-ray diffraction (XRD) powder and differential scanning calorimetry (DSC). The XRD pattern profile analysis had confirm that the CBZ-SAC co-crystal was successfully formed only in ethyl acetate solvent for both of the screening methods applied. The findings also revealed that two polymorphic forms of CBZ-SAC co-crystal was formed during the study